Manipulable preoperative factors affecting surgical outcomes of iStent inject W, particularly the type of antiglaucoma medications - Sayaka Kimura-Uchida; Ryuichi Shimada; Hiroshi Horiguchi; Satoshi Katagiri; Hisato Gunji; Tadashi Nakano (PLoS ONE, 2025)
To analyze the surgical outcomes of iStent inject W (ISIW) implantation and investigate the influence of preoperative factors. In total, 114 eyes of 114 patients (mean age, 73.22 ± 7.84 y) were enrolled in this retrospective study. The patients underwent ISIW implantation at the Jikei University Hospital. The number of antiglaucoma medications was converted into glaucoma medication scores (GMS). Linear mixed model (LMM) analysis was performed by setting GMS and intraocular pressure (IOP) change as objective variables, and the postoperative days, preoperative mean deviation (MD), preoperative IOP, and various antiglaucoma medications as fixed effects. The preoperative IOP was 15.06 ± 3.51 mmHg and significantly reduced to 12.22 ± 2.23 mmHg at 3 months and 12.99 ± 2.45 mmHg at 12 months. The mean GMS was 2.46 ± 1.33 preoperatively, and decreased to 1.32 ± 1.31 at 3 months, and 1.60 ± 1.41 at 12 months postoperatively. The IOP and GMS values were based on a subset of 72 eyes with 12-months of complete follow-up data. LMM analysis showed significant coefficients for IOP change in relation to postoperative days and preoperative IOP, and for GMS change in relation to postoperative days, β blockers (BB), and Rho kinase inhibitors (ROCK inhibitors). Preoperative factors, particularly medication use, influenced outcomes, indicating that BB or ROCK inhibitors were associated with a greater reduction in the need for postoperative antiglaucoma medications.